Fabrication of a laser-directed electrochemical paper analytical device and its deployment for multi-functional electrochemical sensing - Mahapatra S.; Kumari R.; Chandra P. (My University, 2025)
The demand for eco-friendly, disposable, and affordable electrochemical sensors stimulates the fabrication of laser-directed paper-based electrodes. This work reports the fabrication of laser-derived patterns on the paper substrate and its multi-functional sensing applications. For this, a computer-aided design (CAD) software-driven computer numerical control (CNC) manufacturing method was developed to engrave a three-electrode design on a paper substrate. The fabricated Laser-Directed electrochemical Paper Analytical Device (LD-ePAD) was thoroughly characterized by Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), contact angle analysis, electrochemical impedance spectroscopy (EIS), and the cyclic voltammetry (CV). After that, we demonstrated the multi-functional sensing ability of the LD-ePADs by detecting diverse model analytes, including small molecules (i.e., lead ions [Pb2+]), free radicals (i.e., peroxide [H2O2]), and macromolecules (i.e., Alkaline phosphatase [ALP]). Upon investigation, it exhibits a fair detection limit of 5.19 (±0.21) µM for Pb2+, 48.66 (±0.31) µM for H2O2, and 0.48 (±0.02) U/L for ALP. The LD-ePADs' outstanding repeatability, stability, abundance of catalytic active sites, remarkable tunability, and potential for nano-bioengineering emphasized their tremendous commercial feasibility. To the best of our knowledge, this is the first study to use controlled one-step laser direct engraving to fabricate a three-electrode setup on a paper-substrate that can sense three heterogeneous molecules electrochemically. © 2024 Elsevier B.V.